2021
DOI: 10.1111/ppe.12823
|View full text |Cite
|
Sign up to set email alerts
|

The association between wildfire exposure in pregnancy and foetal gastroschisis: A population‐based cohort study

Abstract: Background Global climate change has led to an increase in the prevalence and severity of wildfires. Pollutants released into air, soil and groundwater from wildfires may impact embryo development leading to gastroschisis. Objective The objective of this study was to determine the association between wildfire exposure before and during pregnancy and the risk of foetal gastroschisis development. Methods This was a retrospective cohort study using The California Office of Statewide Health Planning and Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
14
0
2
Order By: Relevance
“…study, 38 which used feeding an infant 0–36 months of age at the time of exposure to wildfire as inclusion criteria. Eight studies focused on local populations exposed to a single, specific wildfire event, 23 – 25 , 28 , 34 , 37 39 whereas seven focused on longer term exposure to wildfire smoke across fire seasons over a span of years, 27 , 30 32 , 35 , 36 and one focused on exposure to mega-fire flame zones (that is, fires over 100,000 acres in size). 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…study, 38 which used feeding an infant 0–36 months of age at the time of exposure to wildfire as inclusion criteria. Eight studies focused on local populations exposed to a single, specific wildfire event, 23 – 25 , 28 , 34 , 37 39 whereas seven focused on longer term exposure to wildfire smoke across fire seasons over a span of years, 27 , 30 32 , 35 , 36 and one focused on exposure to mega-fire flame zones (that is, fires over 100,000 acres in size). 29 …”
Section: Resultsmentioning
confidence: 99%
“…All quantitative studies, as well as the quantitative component of the O’Donnell 23 mixed-methods study, used local administrative neonatal collections for birth statistics. Maternal residential address, 23 , 24 , 32 , 34 ZIP code, 27 , 30 , 33 county, 28 , 29 or maternal municipality 31 , 35 , 36 at time of birth were used as a proxy for nearness to fires or smoke. Each study used a different method to determine exposure to the wildfire disaster or wildfire smoke hazard, including a mix of land-based geographical borders, 23 – 25 , 29 , 30 satellite-based imagery or models, 27 , 28 , 31 36 land-based air quality monitors, 27 , 31 , 33 36 and personal air quality monitors within specific coordinates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue on Climate Change and Reproductive, Perinatal, and Paediatric Health in Paediatric and Perinatal Epidemiology , Park and colleagues 4 provide an investigation of wildfire exposure during pregnancy and risk of gastroschisis in a large cohort of births from 2007 to 2010 in California. They found that residential proximity (<15 miles) to wildfires in the first trimester was associated with a 28% higher risk (relative risk 1.28, 95% confidence interval: 1.07–1.54) of gastroschisis based on ICD‐9 codes from state‐wide data.…”
mentioning
confidence: 99%
“…In the western United States, the frequency and intensity of wildfires have increased dramatically over the past two decades. The manuscript by Park and colleagues 7 links wildfire exposure to foetal gastroschisis, an abdominal wall defect that is rare, but increasing in prevalence. Gastroschisis has been associated with air pollution in some, but not all previous studies.…”
mentioning
confidence: 99%